Porous coating materials

JP2026166140APending Publication Date: 2026-10-14OSAKA GAS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2025058910
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0017】 本発明は、新たに、多孔質塗膜材料を提供する事が出来る。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026166140000001
    Figure 2026166140000001
  • Figure 2026166140000002
    Figure 2026166140000002
  • Figure 2026166140000003
    Figure 2026166140000003
Patent Text Reader

Abstract

The present invention aims to provide a new porous coating material. [Solution] A coating film is provided, comprising (A) a Ti compound and (B) a hydrolysis product of an alkoxysilane, wherein the (A) Ti compound has an average primary particle diameter of 1 nm to 50 nm and is porous. A method for manufacturing the coating film is also provided.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to porous coating materials. [Background technology]

[0002] Patent Document 1 discloses an anti-fogging and anti-stain glass article comprising an alkali-blocking film and a photocatalytic film laminated in that order on the surface of a glass substrate, wherein the surface of the photocatalytic film has irregularities having an arithmetic mean roughness (Ra) of 1.5 to 80 nm and an average spacing (Sm) of irregularities of 4 to 300 nm.

[0003] Patent Document 2 discloses a functional inorganic paint comprising a tetrafunctional silicone resin containing a hydrolyzed polycondensate of a tetrafunctional hydrolyzable organosilane represented by the general formula SiX4, and a curing accelerator, wherein the amount of the tetrafunctional silicone resin is 50% by weight or less of the total amount of paint as total condensed compound equivalent solids, and the amount of the curing accelerator is 2 to 80 parts by weight per 100 parts by weight of the total amount of paint as total condensed compound equivalent solids and total curing accelerator components.

[0004] Patent Document 3 discloses a composition containing a Ti compound, a Si compound, and a solvent, wherein the Si compound is a hydrolysate of an alkylsilane, the Ti compound has a mass loss of 0.1% by mass or more at temperatures above 200°C when the Ti compound is heated to 600°C using a thermogravimetric analysis device, the average primary particle size of the Ti compound is 1 nm to 50 nm, and the solvent is a composition containing water and alcohol. [Prior art documents] [Patent Documents]

[0005] [Patent Document 1] Japanese Patent Publication No. 10-231146 [Patent Document 2] Japanese Patent Publication No. 10-287846 [Patent Document 2] Japanese Patent Publication No. 2024-139342 [Overview of the project] [Problems that the invention aims to solve]

[0006] The present invention aims to provide a new porous coating material. [Means for solving the problem]

[0007] Coatings are used in a variety of applications. For example, coating compositions are particularly used to impart various functions such as antifouling, hydrophilic, and water-repellent effects to the exterior walls and roofs of buildings, the bodies of aircraft, ships, and vehicles, as well as glass, wheels, etc.

[0008] Conventionally, a problem has been that rainbow-like unevenness occurs when there is a difference in refractive index between the coating agent and the substrate. The change in appearance caused by the occurrence of rainbow-like unevenness after film formation is a problem, and there is a demand for a clear coating agent that does not exhibit rainbow-like unevenness.

[0009] The present invention encompasses the following porous coating materials.

[0010] Section 1. A coating film, (A)Ti compound and (B) Contains hydrolysis products of alkoxysilanes, The (A)Ti compound has an average primary particle diameter of 1 nm to 50 nm. A porous coating film.

[0011] Section 2. The aforementioned coating film is (1) The number of voids was found at a magnification of 30,000x under SEM observation, with a unit area of ​​12 μm². 2 There are over 100 winning tickets. (2) The average size of the voids is 10 nm or more. The coating film described in item 1 above.

[0012] Section 3. In the coating paint used to form the aforementioned coating film, The content of the (A) Ti compound is 0.01% by mass to 5% by mass, The content of the hydrolysis product of the (B) alkoxysilane is 0.01% by mass to 20% by mass, The coating film according to the above item 1 or 2.

[0013] Item 4. The coating film according to the above item 1 or 2, wherein the hydrolysis product of the (B) alkoxysilane is a hydrolysis product of tetraethyl orthosilicate (TEOS).

[0014] Item 5. The coating film according to the above item 1 or 2, which is an antibacterial and antiviral coating film.

[0015] Item 6. A method for producing the coating film according to the above item 1 or 2, comprising: (1) a step of synthesizing a Ti compound in a solvent, attaching an organic chain to the Ti compound, and then producing titania-coated silver, and (2) after the step (1), a step of mixing the organic chain-bonded titania-coated silver and alkoxysilane in a solvent, then hydrolyzing the alkoxysilane to prepare a coating material for forming a coating film, and (3) a step of forming a porous coating film using the coating material obtained in the step (2) The method for producing a coating film, comprising the steps above.

[0016] The porous coating film of the present invention is a porous coating film based on a hybrid configuration of silica and titania by a sol-gel method, and is a coating material that suppresses light interference and prevents rainbow unevenness. [Advantageous Effects of Invention]

[0017] The present invention can newly provide a porous coating film material. [Mode for Carrying Out the Invention]

[0018] Hereinafter, the present invention will be described in detail.

[0019] The embodiments illustrating the present invention are intended to provide a better understanding of the invention's intent and, unless otherwise specified, do not limit the scope of the invention.

[0020] In this specification, "contains" and "include" are concepts that encompass all of "comprise," "consist essentially of," and "consist of."

[0021] In this specification, when a numerical range is indicated as "A to B", it means "greater than or equal to A and less than or equal to B".

[0022] In this specification, when using indications such as parts, percentages, etc., they represent parts by mass, parts by weight, mass%, or weight% (wt%).

[0023] [1] Paint film (paint for forming paint film) Coatings are used in a variety of applications. For example, coating compositions are particularly used to impart various functions such as antifouling, hydrophilic, and water-repellent effects to the exterior walls and roofs of buildings, the bodies of aircraft, ships, and vehicles, as well as glass, wheels, etc.

[0024] Conventionally, a problem has been that rainbow-like unevenness occurs when there is a difference in refractive index between the coating agent and the substrate. The change in appearance caused by the occurrence of rainbow-like unevenness after film formation is a problem, and there is a demand for a clear coating agent that does not exhibit rainbow-like unevenness.

[0025] The coating film (porous coating material) of the present invention is (A)Ti compound and (B) Contains hydrolysis products of alkoxysilanes, (A) The Ti compound has an average primary particle size of 1 nm to 50 nm. It is porous.

[0026] The coating film of the present invention is preferably, (1) The number of voids was found at a magnification of 30,000x under SEM observation, with a unit area of ​​12 μm². 2 There are over 100 winning tickets. (2) The average size of the voids is 10 nm or more.

[0027] The coating film of the present invention is preferably made in a coating film-forming paint that forms the coating film. (A) The Ti compound has a content of 0.01% to 5% by mass, (B) The hydrolysis product of the alkoxysilane has a content of 0.01% to 20% by mass.

[0028] In the present invention, the hydrolysis product of (B) alkoxysilane is preferably a hydrolysis product of tetraethyl orthosilicate (TEOS).

[0029] The coating film of the present invention is preferably an antibacterial and antiviral coating film.

[0030] The coating film of the present invention is a porous coating film produced by the sol-gel method using a hybrid structure of silica and titania, which suppresses light interference and prevents rainbow-like unevenness.

[0031] (1-1)(A)Ti compound The coating film (coating film-forming paint) of the present invention contains (A)Ti compound, and the average primary particle size of the (A)Ti compound is 1 nm to 50 nm.

[0032] Water, inorganic acids, and liberated organic acids generally evaporate almost completely below 200°C.

[0033] (A) The titania compound (titania nanoparticles) of the Ti compound (preferably titania-coated silver) has acetyl groups (CH3-C(=O)-, Ac), acetoxy groups (acetyloxy group, CH3-C(=O)-O-, AcO), etc. bonded to at least some of the titanium atoms present on its surface, and these gradually detach in the range of 200°C to 600°C. For example, in the case of acetoxy groups, they gradually detach in the range of 200°C to 600°C, with a peak at approximately 260°C.

[0034] Titania compounds can improve the dispersibility of titania particles by imparting organic matter to the fine titania surface. Preferably, the titania compound has organic chains such as acetyl groups and acetoxy groups bonded to at least some of the titanium atoms on its surface, which suppresses aggregation of titania nanoparticles during drying or firing, making it less prone to cracking and peeling, and resulting in excellent coatability and transparency. Because the titania compound can suppress cracking and peeling and easily support metals, it also exhibits excellent visible photocatalytic activity.

[0035] Titania compounds are particularly effective at suppressing cracks and peeling because they can inhibit the aggregation of titania nanoparticles during drying or calcination.

[0036] Titania compounds, when at least some of the titanium atoms on their surface have organic chains such as acetyl groups or acetoxy groups, gradually detach in the range of 200°C to 600°C. Therefore, when heated, differential thermogravimetric analysis (TG-DTA) shows a large mass loss above 200°C.

[0037] For titania compounds, the mass loss at temperatures above 200°C, as measured by differential thermogravimetric analysis (TG-DTA), indicates the number of organic chains, such as acetyl groups and acetoxy groups, bonded to titanium atoms on the surface.

[0038] In water-repellent coatings, the titanium (Ti) compound contained in (A)Ti compound preferably exhibits a mass loss of 1% by mass or more at temperatures above 200°C when the Ti compound is heated to 600°C using a differential thermogravimetric analyzer (TG-DTA). The mass loss of the Ti compound at temperatures above 200°C when heated to 600°C using a differential thermogravimetric analyzer (TG-DTA) is 0.1% by mass or more, preferably 1% by mass or more, and more preferably 5% by mass or more. The upper limit of the mass loss of the Ti compound is preferably 20% by mass.

[0039] The detailed conditions for the differential thermogravimetric simultaneous thermometry device (TG-DTA) are: atmosphere: air, heating rate: 3°C / min.

[0040] The organic chains (acetyl groups, acetoxy groups, etc.) present on the surface of the Ti compound are preferably acetyl groups (CH3-C(=O)-), acetoxy groups (CH3-C(=O)-O-), etc., from the viewpoint of water solubility, odor, volatility, harmfulness, and decomposability.

[0041] The organic chain may have at least one organic chain selected from the group consisting of the aforementioned organic chains attached to it. These organic chains may be attached individually, or two or more organic chains may be attached depending on the purpose.

[0042] In the coating film (paint for forming a coating film), (A) the average primary particle size of the Ti compound is 1 nm to 50 nm, preferably 1 nm to 20 nm, and more preferably 1 nm to 10 nm. By adjusting the average primary particle size of the Ti compound to this range, it becomes possible to partially coat the silver with Ti. The titania nanoparticles can form a film with higher visible photocatalytic activity and higher transparency. The Ti compound has excellent coatability.

[0043] The average primary particle size of the Ti compound (titania nanoparticles) is measured by electron microscopy (TEM) observation. The average primary particle size is calculated as follows:

[0044] First, adjust the magnification of the electron microscope to a level where the particles are clearly visible and take an image. Load the captured image into image processing software such as WINROOF. Then, use the shape measurement function to evaluate the shape of the particles. The equivalent circle diameter (Heywood system) calculated therein is defined as the particle diameter of the particle. Perform this operation on any 20 particles and define the average as the average primary particle diameter.

[0045] The specific surface area of ​​the Ti compound is preferably 150 m². 2 / g~500m 2 It is / g, more preferably 200m 2 / g~400m 2The value is / g. By adjusting the specific surface area of ​​the Ti compound to this range, it is possible to coat the Ti compound with metals (silver and copper) to an appropriate degree, partially coating the silver with Ti. The Ti compound exhibits high visible photocatalytic activity.

[0046] The specific surface area of ​​the Ti compound is measured by the BET method.

[0047] The concentrations of N, Cl, and S in the Ti compound can be preferably 0 to 5,000 ppm, more preferably 0 to 1,000 ppm. By adjusting the concentrations of N, Cl, and S in the Ti compound to this range, corrosion of the substrate can be suppressed. The concentrations of N, Cl, and S in the Ti compound mean that impurities derived from acidic Ti compound precursors such as TiCl4 and TiOSO4 are absent or present in very small amounts.

[0048] The concentrations of N, Cl, and S elements in Ti compounds are measured by WDX (X-ray fluorescence).

[0049] The crystalline form of the Ti compound is preferably the anatase form. The Ti compound (titania nanoparticles) is preferably the anatase form, more preferably a crystalline form containing 90% or more of the anatase form, and even more preferably a crystalline form that contains no crystalline forms other than the anatase form and is 100% anatase form. By using the anatase form of the Ti compound, the visible photocatalytic activity of the Ti compound is improved.

[0050] (1-2)(B) Hydrolysis products (binders) of alkoxysilanes The coating film (coating film-forming paint) of the present invention contains (B) a hydrolysis product (binder) of an alkoxysilane (alkylsilane).

[0051] Water-repellent coatings contain Ti compounds (titania particles), and by applying organic matter to the fine titania surface, the dispersibility of the titania particles can be improved. By mixing Ti compounds (titania particles) with alkoxysilane, which is a raw material for the hydrolysis product (binder) of (B) alkoxysilane, a titania particle composite binder can be produced by carrying out a hydrolysis reaction while maintaining high dispersibility through the coexistence of both. Water-repellent coatings can improve the aggregation of titania, and can greatly improve solvent stability and adhesion.

[0052] (B) The hydrolysis products of the alkoxysilane are preferably trialkoxysilanes such as methyltrimethoxysilane (MTMS), methyltriethoxysilane (MTES), ethyltrimethoxysilane (ETMS), phenyltriethoxysilane (PhTES), vinyltriethoxysilane (VTES), n-propyltrimethoxysilane (n-PrTMS), and isopropyltrimethoxysilane (iso-PrTMS).

[0053] (B) The hydrolysis products of the alkoxysilane are preferably dialkoxysilanes such as dimethyldiethoxysilane (DMDE), diphenyldimethoxysilane (DPhDM), and methylethyldimethoxysilane (MEDM).

[0054] (B) The hydrolysis product of the alkoxysilane is preferably a monoalkoxysilane such as trimethylmethoxysilane (TMMS).

[0055] (B) Hydrolysis products of alkoxysilanes are preferably methyltrichlorosilane, phenyltrichlorosilane, vinyltrichlorosilane, dimethyldichlorosilane, diphenyldichlorosilane, trimethylchlorosilane, tetraethoxysilane, etc.

[0056] (B) The hydrolysis products of the alkoxysilane are preferably hexyltrimethoxysilane, octyltrimethoxysilane, dodecyltrimethoxysilane, octadecyltrimethoxysilane, hexadecyltrimethoxysilane, hexyltriethoxysilane, octyltriethoxysilane, dodecyltriethoxysilane, octadecyltriethoxysilane, hexadecyltriethoxysilane, etc.

[0057] (B) The hydrolysis product of the alkoxysilane is preferably the hydrolysis product of TEOS (tetraethyl orthosilicate, tetraethoxysilane).

[0058] (B) The hydrolysis product of the alkoxysilane may be at least one compound selected from the group consisting of the alkoxysilanes, and these alkoxysilanes may be used individually or two or more may be mixed (blended) depending on the purpose.

[0059] (1-3)(C) Solvent The coating film (coating film-forming paint) of the present invention preferably contains (C) a solvent, and (C) is at least one solvent selected from the group consisting of water and alcohols.

[0060] The alcohols are preferably aliphatic alcohols having 1 to 6 carbon atoms such as methanol, ethanol, propanol, and isopropanol, and non-aliphatic alcohols such as α-terpineol; glycol solvents such as butyl carbitol (diethylene glycol monobutyl ether), hexylene glycol (2-methyl-2,4-pentanediol), ethylene glycol-2-ethylhexyl ether, ethylene glycol monomethyl ether, and propylene glycol monomethyl ether; and diols such as 1,4-butanediol, 1,5-pentanediol, and 1,6-hexanediol.

[0061] The alcohol may be at least one compound selected from the group consisting of the aforementioned alcohols, and these alcohols may be used individually or mixed (blended) with two or more depending on the purpose.

[0062] In the case of coatings (paints for forming coatings), it is also possible to change the solvent. Water can be removed from the reaction solution by centrifuging or filtration of water-repellent paints and replaced with an organic solvent.

[0063] (1-4) Paint film (paint for film formation) The coating film (coating film-forming paint) of the present invention preferably contains (A)Ti compound in a water-repellent paint with a content of 0.01% to 5% by mass.

[0064] The coating film (coating film-forming paint) of the present invention preferably contains (B) a hydrolysis product of alkoxysilane in an amount of 0.01% to 20% by mass.

[0065] (1-5) Coating film (paint for forming coating film), antibacterial and antiviral coating film In the coating film (coating film-forming paint) of the present invention, the dispersibility of the Ti compound (titania particles) can be improved by applying organic matter to the fine titania surface. By mixing the Ti compound (titania particles) with an alkoxysilane, which is a raw material for the binder, and carrying out a hydrolysis reaction while maintaining high dispersibility through the coexistence of the two, a titania particle composite binder can be produced.

[0066] The coating (film-forming paint) can improve the aggregation of titania, significantly improving the solvent stability of the paint and the adhesion of the coating. The coating (film-forming paint) has good dispersibility, resulting in excellent crack resistance of the coating. The coating (film-forming paint) also enables the formation of a dense titania coating, and in addition to excellent applicability and transparency, it also exhibits excellent visible photocatalytic activity.

[0067] In coating films (paints for forming coating films), the content of (A)Ti compounds is preferably 0.01% to 5% by mass in the composition, from the viewpoint of ease of coating and film properties of the coating.

[0068] In the coating film (paint for forming a coating film), the content of (B) alkoxysilane hydrolysis products is preferably 0.01% to 20% by mass in the composition, from the viewpoint of ease of coating and film properties of the coating.

[0069] In water-repellent coatings, the ratio of (A)Ti compound to (B)alkoxysilane hydrolysis product in the composition is preferably such that, from the viewpoint of ease of coating and film properties of the coating, (A)Ti compound is present in a mass ratio of 0.02 to 20 (0.02 to 20 parts by mass) per (1 part by mass) of (B)alkoxysilane hydrolysis product, and more preferably, (A)Ti compound is present in a mass ratio of 0.1 to 1 (0.1 to 1 part by mass).

[0070] The pH of the coating (dispersion) for film formation varies depending on the type and amount of metal added, and from the viewpoint of coatability, it is preferably 1 to 5, and more preferably 2 to 4.

[0071] The present invention encompasses an antibacterial and antiviral coating film containing the water-repellent coating of the present invention.

[0072] The coating film (coating film-forming paint) of the present invention is preferably prepared by adjusting its viscosity according to the application. When the paint is used for application by spin coating, dip coating, spraying, etc., it is preferably prepared to have a low viscosity. When the paint is used for application by brush coating, squeegeeing, etc., it is preferably prepared to have a higher viscosity. When the paint is used for application by screen printing, it is preferably prepared to have an even higher viscosity to suppress fluidity.

[0073] The coating film of the present invention enables a dense coating.

[0074] This invention includes an antibacterial and antiviral coating film.

[0075] Painted products having a coating film are not particularly limited and include, for example, building materials, building exteriors, building interiors, window frames, window glass, various lenses, structural members, building equipment such as houses, cooking utensils, textile products, furniture, displays, display protective films, plumbing components, covers and window glass for vehicle lighting, machinery or exteriors of articles, dust covers and coatings, display equipment and their covers, traffic signs, various display devices, advertising towers and other display objects, sound barriers for roads and railways, bridges, guardrail exteriors and coatings, tunnel interiors and coatings, insulators, solar cell covers, solar water heater collector covers and other exterior parts of electronic and electrical equipment used outdoors, especially transparent members, vinyl greenhouses, greenhouses and the like.

[0076] (1-6) (1) Number of voids in the coating film, (2) Average size of the voids The coating film (porous coating film) of the present invention preferably has (1) a number of voids of 12 μm² per unit area at a magnification of 30,000x SEM observation. 2 Correct (Observation area: 4 μm wide × 3 μm high = 12 μm) 2 ), there are more than 100 of them.

[0077] The coating film (porous coating film) of the present invention preferably has (2) an average void size of 10 nm or more.

[0078] (1) Number of voids in the coating film (Method for measuring coating film) A coating agent is applied to a Si substrate to form a coating film (porous coating film), and an image is taken using an electron microscope (scanning electron microscope (SEM) or transmission electron microscope (TEM)) to observe the shape of the coating film at a magnification of 30,000.

[0079] Subsequently, the image is binarized using image processing software such as WinROOF (Mitani Corporation). While this binarization is performed manually, line analysis is conducted at arbitrary points to obtain density cross-sectional diagrams as a guideline.

[0080] [ka]

[0081] Regarding the voids in the coating film, they are detected as relatively low GRAY values in an electron microscope image. The D10 value of the GRAY values is taken as the binarization threshold. When a porous coating film is formed, a large number of domain voids exist, and a large number of particles are measured.

[0082]

Chemical formula

[0083] (Method for measuring the number of voids) After the binarization treatment, "circular separation", which is a function for separating overlapping particles, is performed. Thereby, the influence of overlapping particles is separated, and the number of voids can be measured. Subsequently, the number of voids is measured using the "shape feature" function.

[0084] In the coating film of the present invention, preferably, (1) the number of voids is, at a magnification of 30,000 times in SEM observation, per unit area of 12 μm 2 or more, 100 or more, more preferably 500 or more, still more preferably 1,000 or more, and particularly preferably 3,000 or more. The larger the number of voids, the higher the adsorption effect, and the more it is possible to prevent rainbow unevenness caused by light interference.

[0085] In the coating film of the present invention, (1) the number of voids is preferably, per unit area of 12 μm 2 or less, 10,000 or less, more preferably about 7,000 or less.

[0086] (2) Average size of voids in the coating film (Method for measuring the average size of voids) After the binarization treatment, "circular separation", which is a function for separating overlapping particles, is performed. Thereby, the influence of overlapping particles is separated, and the shape of the voids can be measured. Subsequently, the average size of the voids is measured using the "shape feature" function. For the average size of the voids, the average value of the equivalent circle diameters measured by the shape measurement function is taken as the average size.

[0087] The coating film of the present invention preferably has an average void size of 10 nm or more, more preferably 10 nm to 1,000 nm, even more preferably 10 nm to 100 nm, and particularly preferably 10 nm to 30 nm. If the average void size is too small, iridescence will occur due to interference effects of the film, and the adsorption effect will also tend to decrease. If the average void size is too large, the specific surface area will decrease, and the adsorption effect will tend to decrease.

[0088] [2] Method for manufacturing the coating film The method for producing the coating film (porous coating material) of the present invention is a method for producing the coating film (porous coating material) of the present invention. (1) A step of synthesizing a Ti compound in a solvent, attaching an organic chain to the Ti compound, and then producing titania-coated silver, and (2) After step (1), a step of mixing the titania-coated silver to which the organic chain is bonded with an alkoxysilane in a solvent, and then hydrolyzing the alkoxysilane to produce a paint that forms a coating film, and (3) The process includes a step of forming a porous coating film using the paint obtained in step (2).

[0089] The method for producing the coating film (porous coating material) of the present invention preferably includes in step (2) a step of performing a high-pressure dispersion treatment thereafter, which involves dispersing a dispersion containing titania-coated silver.

[0090] Titania-coated silver is a material in which a portion of the surface of silver (Ag) nanoparticles is coated with titania.

[0091] (2-1) (1) A step of synthesizing a Ti compound in a solvent, attaching an organic chain to the Ti compound, and then producing titania-coated silver. In the method for producing the coating film (porous coating material) of the present invention, first, organic matter is applied to the fine titania surface to improve the dispersibility of titania particles.

[0092] (A Ti compound is synthesized in a solvent, and an organic chain is added to the Ti compound.) In step (1), organic chains are bonded to the surface of the Ti compound in a solvent.

[0093] The Ti compound (a substance containing titanium) is preferably a substance that becomes titanium oxide upon heating. The titanium-containing substance is preferably titanium oxide and / or a titanium oxide precursor, and more preferably titanium oxide; titanium hydroxide; titanium alkoxide; titanium halides such as titanium trichloride and titanium tetrachloride (especially those neutralized with a base); or metallic titanium.

[0094] From the viewpoint of the dispersibility, coatability, and visible photocatalytic properties of the resulting titania, the titanium-containing substance is preferably titanium alkoxide, titanium hydroxide, or titanium halide (especially those neutralized with a base). From the viewpoint of purity, dispersibility, coatability, transparency, and visible photocatalytic properties, the titanium-containing substance is more preferably titanium alkoxide.

[0095] The titanium alkoxide is preferably titanium tetraisopropoxide, titanium tetra-n-butoxide, titanium tetra-n-propoxide, or titanium tetraethoxide. From the viewpoint of cost, water solubility of by-products, applicability, and visible photocatalytic properties, titanium tetraisopropoxide is more preferable.

[0096] The Ti compound may be at least one compound selected from the group consisting of the aforementioned Ti compounds, and these Ti compounds may be used individually or two or more may be mixed (blended) depending on the purpose.

[0097] The average primary particle size of the Ti compound is preferably 100 nm or less, and more preferably 50 nm or less. There is no specific lower limit set for the average primary particle size of the titanium-containing material, but it is preferably about 1 nm. If the particle size is large, it is preferably ground dry or wet using a planetary ball mill, paint shaker, etc.

[0098] The average primary particle size of Ti compounds (solids such as titanium oxide, metallic titanium, and titania nanoparticles) is measured by electron microscopy (TEM). The average primary particle size is calculated as follows:

[0099] First, adjust the magnification of the electron microscope to a level where the particles are clearly visible and take an image. Load the captured image into image processing software such as WINROOF. Then, use the shape measurement function to evaluate the shape of the particles. The equivalent circle diameter (Heywood system) calculated therein is defined as the particle diameter of the particle. Perform this operation on any 20 particles and define the average as the average primary particle diameter.

[0100] The concentration of the Ti compound in the dispersion is preferably 0.01 mol / L to 5 mol / L, and more preferably 0.05 mol / L to 3 mol / L, from the viewpoint of productivity, viscosity of the reaction solution, coatability, transparency, and visible photocatalytic properties.

[0101] The acid used in the reaction is an organic acid, and a volatile acid is preferred; therefore, a chemical formula C is preferred. n H 2n+1 Monocarboxylic acids represented by COOH(n=0~3) (monocarboxylic acids with 1 to 4 carbon atoms), hydroxycarboxylic acids with 2 to 3 carbon atoms, etc. are used.

[0102] From the viewpoint of volatility, toxicity, and degradability, the monocarboxylic acids are preferably formic acid with n=0 and acetic acid with n=1.

[0103] The hydroxycarboxylic acid is preferably glycolic acid, lactic acid, etc., and more preferably acetic acid, glycolic acid, lactic acid, etc., from the viewpoint of water solubility and odor.

[0104] The organic acid may be at least one compound selected from the group consisting of the aforementioned organic acids, and these organic acids may be used individually or two or more may be mixed (blended) depending on the purpose.

[0105] The amount of organic acid used is adjusted so that, from the viewpoint of dispersibility, coatability, transparency, visible photocatalytic properties, and cost, the number of moles of acyloxy groups in the Ti compound is preferably 1.5 moles or more, and particularly preferably 2 moles or more, per mole of titanium. The more organic acid used, the better the long-term stability, coatability, transparency, etc. can be improved. There is no particular upper limit to the amount of organic acid used, but it is preferably adjusted so that the number of moles of acyloxy groups in the Ti compound is 10 moles or less per mole of titanium.

[0106] The concentration of the organic acid in the dispersion is preferably 0.02 mol / L to 10 mol / L, and more preferably 0.1 mol / L to 7 mol / L, from the viewpoints of dispersibility, coatability, transparency, visible photocatalytic properties, and cost.

[0107] The reaction solvent is preferably an aqueous solvent such as water, mainly composed of (preferably 50% by mass or more). The reaction solvent may also contain alcohol or ester during the reaction.

[0108] When titanium tetraisopropoxide is used as the reaction solvent, isopropyl alcohol is produced by reaction with organic acids. Isopropyl esters of organic acids may be produced by heating. Alcohols or esters may be added to the dispersion, or they may be generated in the system. Alcohols or esters may be removed by heating in an open system below 100°C, by reducing the pressure, or they may remain in the reaction solution.

[0109] When alcohol is present in the dispersion, the average primary particle size of the resulting Ti compound (titania nanoparticles) tends to decrease. Therefore, alcohol may be intentionally added to control the average primary particle size.

[0110] The pH of the dispersion is preferably 2 or higher and less than 6, and more preferably 2.1 to 5, from the viewpoint of preventing corrosion of the equipment, ensuring safety during handling, and maintaining dispersibility.

[0111] The method for preparing the dispersion is not particularly limited; the Ti compound, organic acid, and water (solvent) may be mixed simultaneously or sequentially. In mass production, from the viewpoint of preventing aggregation and the formation of large clumps, and facilitating continued stirring, it is preferable to mix the organic acid and water (solvent) first, and then add the titanium-containing substance while stirring. In laboratory scale, it is preferable to mix the titanium-containing substance and the organic acid first, and then add the water while stirring.

[0112] (Preparing titania-coated silver) Titania-coated silver is produced by irradiating a composite of a Ti compound and a silver compound with ultraviolet light. In the water-repellent coating of the present invention, (A) the Ti compound preferably has a structure in which a titania compound is supported around silver nanoparticles (carrier), or a structure in which titania coats the silver nanoparticles (carrier) (titania-coated silver).

[0113] High-pressure dispersion method (pressure treatment) It is desirable to disperse Ti compounds (titania compounds) using a dispersion device that generates high pressure through collisions between particles to disperse them. For example, this can be done with a jet mill, and by doing so, titania particles can be highly dispersed in a liquid, making it possible to partially coat the material with titania.

[0114] A dispersion containing a Ti compound (preferably titania fine particles) is subjected to a pressure treatment of 30 MPa or higher (high-pressure dispersion method).

[0115] The Ti compound becomes finer when subjected to pressure treatment.

[0116] The pressure level during the pressurization treatment is not particularly limited, as long as it is sufficient to adequately atomize the Ti compound. Preferably, the pressure level is adjusted to 30 MPa or higher, more preferably to 50 MPa to 400 MPa, and even more preferably to 100 MPa to 300 MPa. The pressurization treatment is preferably carried out using a high-pressure dispersion device. A high-pressure dispersion device can disperse the Ti compound by applying mechanical pressure.

[0117] By pressurizing, for example, (i) Colliding two or more dispersions of Ti compounds with each other, (ii) Colliding a dispersion of a Ti compound with a metal or ceramic material (high-hardness material such as silicon carbide or alumina), (iii) Dispersion of Ti compound with a cross-sectional area of ​​1 cm² 2 Passing through the following space Perform processes such as those described above.

[0118] By applying pressure, it is possible to increase the pressure conditions, which allows for more efficient atomization of Ti compounds and further reduces processing time.

[0119] The pressurization operation is preferably performed once or more times, and more preferably 10 times or more.

[0120] The pressurizing temperature is not particularly limited. The pressurizing temperature is adjusted to a temperature that allows for sufficient thinning of the carbonaceous material having a layered structure. The pressurizing temperatures in (i) and (ii) are preferably adjusted to 0°C to 100°C, more preferably to 20°C to 95°C. When mechanically applying pressure, the pressurizing temperature in (iii) is preferably adjusted to 0°C to 100°C. When pressure is generated by a supercritical state of water, the pressurizing temperature in (iii) is preferably adjusted to 373°C to 700°C, more preferably to 380°C to 450°C.

[0121] When performing pressurized treatment, it is preferable to perform ultrasonic dispersion treatment on the dispersion containing the Ti compound as a preliminary treatment (pretreatment) to atomize the Ti compound. This can have effects such as preventing clogging in high-pressure dispersion devices, supercritical water production devices, etc.

[0122] The output power during ultrasonic dispersion treatment is not particularly limited. From the viewpoint of atomizing the Ti compound, the output power during ultrasonic dispersion treatment is preferably adjusted to be stronger than that of typical ultrasonic dispersion treatment (approximately 40W to 50W). The output power of the ultrasonic dispersion treatment is preferably adjusted to 100W or more, more preferably to 300W to 20,000W, and even more preferably to 400W to 18,000W.

[0123] The ultrasonic dispersion temperature is not particularly limited. Preferably, the ultrasonic dispersion temperature is adjusted to a temperature that allows for sufficient atomization of the Ti compound. Preferably, the ultrasonic dispersion temperature is adjusted to 0°C to 80°C, and more preferably to 10°C to 70°C.

[0124] The ultrasonic dispersion time is not particularly limited. Preferably, the ultrasonic dispersion time is adjusted to a time that allows for sufficient atomization of the Ti compound. Preferably, the ultrasonic dispersion time is adjusted to 1 minute to 600 minutes, and more preferably to 3 minutes to 120 minutes.

[0125] As a pre-treatment or post-treatment for these processes, other dispersion methods such as conventional mechanical stirring, dispersion using an emulsifier, or dispersion using a bead mill may be used in combination.

[0126] UV light irradiation Ultraviolet (UV) light irradiation is preferably carried out at room temperature (below 20°C), more preferably at 15°C or below, from the viewpoint of ease of supporting silver on the Ti compound (titania nanoparticles) (titania-coated silver), visible photocatalytic activity, reaction rate, productivity, controllability of aspect ratio, resistance to discoloration during low-intensity UV irradiation, visibility during high-intensity UV irradiation, and re-transparency in UV-free environments. The lower limit of the UV light irradiation temperature is not particularly limited, but is preferably 0°C when reacting at atmospheric pressure. When UV light irradiation is carried out, stirring is preferably performed from the viewpoint of ensuring sufficient reaction between the dispersion and the silver salt. The method of stirring is not particularly limited and can be carried out according to conventional methods.

[0127] The reaction time for ultraviolet light irradiation is preferably 1.5 hours or more, and more preferably in the range of 1.5 hours to 36 hours. By adjusting the reaction time to 1.5 hours or more, inorganic oxide fine particles are well supported around the silver nanoparticles, and gelation of the silver nanoparticles does not occur. By adjusting the reaction time to within 36 hours, the particle size of the silver nanoparticles is adjusted, and precipitation of the silver nanoparticles does not occur.

[0128] From the viewpoint of ease of loading, reaction rate, reaction controllability, and productivity, an ultraviolet irradiation device containing wavelengths of 280 nm to 500 nm is preferably used. By adjusting the wavelength of the ultraviolet light to a range of 280 nm or higher, the dispersion stability of titania-coated silver is good. By adjusting the wavelength of the ultraviolet light to a range of 500 nm or lower, the silver is well reduced and silver nanoparticles are well generated.

[0129] Preferably, the composition of the present invention further contains at least one metal selected from the group consisting of silver, copper, and platinum.

[0130] When using a silver salt as the silver compound, the silver salt is preferably an acidic or neutral silver salt in aqueous solution. Preferably, the silver salt is silver(I) chloride, silver(I) nitrate, silver organic acid (silver(I) lactate, silver(I) acetate, silver(I) citrate, silver(I) myristate, etc.), silver(I) sulfide, silver(I) oxide, silver(I) phosphate, silver(I) carbonate, silver(I) bromide, silver(I) iodide, etc. The silver salt may be at least one compound selected from the group consisting of the above silver salts, and these silver salts may be used individually or mixed (blended) with two or more depending on the purpose.

[0131] The amount of silver salt used is preferably 50% by mass or less relative to the titanium oxide in the Ti compound (titania nanoparticles), more preferably 0.01% to 40% by mass, and even more preferably 0.01% to 25% by mass, based on the mass of silver element in the silver salt, from the viewpoint of dispersibility, transparency, antimicrobial activity (antimicrobial activity and antiviral activity), and stability of the Ti compound (titania nanoparticles). By adjusting the amount of silver salt used within this range, it is possible to easily maintain coatability and transparency, and to particularly improve antimicrobial activity, antiviral activity, and photocatalytic activity in the dark.

[0132] Titania-coated silver can be recovered by conventional methods, such as precipitation and centrifugation. Organic chains are bonded to titanium atoms present on the surface, and (A) titania-coated silver has a structure in which a titania compound is supported around silver nanoparticles (carriers), or a structure in which titania coats the silver nanoparticles (carriers).

[0133] (2-2) (2) After step (1), the titania-coated silver to which the organic chain is attached and the alkoxysilane are mixed in a solvent, and then the alkoxysilane is hydrolyzed. In step (2), the titania-coated silver with an organic chain attached is mixed with an alkoxysilane in a solvent, and the alkoxysilane is hydrolyzed (preparation of the coating solution).

[0134] In the manufacturing process, titania particles and alkoxysilane, which is a raw material for the binder, are mixed together. By maintaining high dispersibility through the coexistence of the two, a hydrolysis reaction is carried out to produce a titania particle composite binder.

[0135] Hydrolysis is preferably carried out by covering the dispersion with a lid to prevent the solvent from evaporating and maintaining the dispersion at a temperature of about 65°C for about 15 hours.

[0136] Hydrolysis is preferably carried out under normal pressure or under pressure in a sealed container.

[0137] The pH of the dispersion is preferably 2 or higher and less than 6, and more preferably 2.1 to 5, from the viewpoint of preventing corrosion of the equipment, ensuring safety during handling, and maintaining dispersibility.

[0138] In titania-coated silver, organic substances (acetyl groups, acetoxy groups, etc.) bound to the surface of the Ti compound (titania) react with alkoxysilane, and the hydrolysis of the alkoxysilane proceeds (hydrolyzed product), resulting in a transparent coating solution.

[0139] (High-pressure dispersion treatment is performed to disperse the dispersion containing titania-coated silver.) Preferably, the coating liquid can be subjected to high-pressure dispersion treatment (high-pressure dispersion method) to obtain a transparent dispersion.

[0140] (2-3) (3) A process to form a porous coating film using the paint obtained in step (2). The coating film (porous coating material) of the present invention forms a porous coating film.

[0141] The coating film (coating film-forming paint) of the present invention is preferably prepared by adjusting its viscosity according to the application. When the paint is used for application by spin coating, dip coating, spraying, etc., it is preferably prepared to have a low viscosity. When the paint is used for application by brush coating, squeegeeing, etc., it is preferably prepared to have a higher viscosity. When the paint is used for application by screen printing, it is preferably prepared to have an even higher viscosity to suppress fluidity.

[0142] The manufacturing method of the present invention, by producing a composition containing titania particles through a novel process, can improve the aggregation of titania, which has been a problem in the past, and can greatly improve solvent stability and adhesion. [Examples]

[0143] The present invention will be specifically described below with reference to examples.

[0144] The present invention is not limited to the following specific embodiments.

[0145] [1] Manufacturing of porous coatings [Example 1] (Step 1) Method for preparing photocatalytic titanium dioxide 0.5 mol of titanium tetraisopropoxide ((A)Ti compound, amount of titanium tetraisopropoxide added in the preparation method for photocatalytic titanium oxide (mol)) was added and stirred. Then, water was added until the total volume was 800 g, and the mixture was stirred for 90 minutes. Next, the reaction mixture was heated to 95°C and stirred with a hot stirrer for 9 hours to obtain a homogeneous titania sol. The obtained sol was subjected to ultrasonic dispersion for 30 minutes to obtain a transparent titania sol.

[0146] The TG-DTA of the obtained titania sol was measured after heating it to 600°C under an air atmosphere at a rate of 3°C / min. The mass loss rate above 200°C was 10% by mass. This mass loss rate above 200°C is due to organic matter derived from acetic acid bound to the titania surface. To adjust the concentration of the obtained titania sol, it was diluted with water to obtain a titania sol with a TiO2 concentration of 2% by mass (wt%).

[0147] When the particle size of the obtained titania sol was observed by TEM, the average primary particle size was found to be 5 nm.

[0148] (Step 2) Compounding with metal ions To the titania sol prepared as described above, with a TiO2 concentration of 2% by mass, silver nitrate was added so that the weight ratio of Ag / TiO2 was 0.01, and the mixture was thoroughly stirred until the whole was homogeneous. Next, the titania sol was irradiated with an ultraviolet lamp for 24 hours to reduce the silver nitrate and obtain a silver-compound titania sol.

[0149] (Step 3) Preparation of coating solution To the 2% by mass silver-compound titania sol prepared above, tetraethyl orthosilicate (TEOS) was added. Then, ethanol was added until the total volume reached 300 g. At this time, the content of the Ti compound and the Si compound were adjusted to 0.8 wt% (Ti compound) and 1.6 wt% (Si compound), respectively. After that, the reactor was covered to prevent the solvent in the reaction solution from evaporating, and it was maintained at 60°C for 1 hour. The organic matter bound to the titania surface reacted with tetraethyl orthosilicate, and the hydrolysis of tetraethyl orthosilicate ((B) hydrolysis product of alkoxysilane) proceeded, yielding a transparent coating solution.

[0150] The obtained liquid was subjected to high-pressure dispersion treatment (high-pressure dispersion method), and a clear dispersion was obtained.

[0151] [Example 2] In Example 2, the coating solution was prepared using the same process as in Example 1, except that the reaction temperature in step 1 of Example 1, specifically the method for preparing the photocatalytic titanium dioxide, was changed to 80°C.

[0152] [Example 3] Example 3 was prepared using the same process as in Example 1, except that the reaction temperature in step 1 of Example 1, specifically the method for preparing the photocatalytic titanium dioxide, was changed to 60°C.

[0153] [Example 4] Example 4 was prepared using the same process as in Example 1, except that in step 3 of Example 1, the content of the Ti compound and the Si compound were changed to 1.6 wt% (Ti compound) and 3.2 wt% (Si compound), respectively.

[0154] [Example 5] In Example 5, the coating solution was prepared using the same process as in Example 1, except that in step 3 of Example 1, the content of the Ti compound and the Si compound were changed to 0.2 wt% (Ti compound) and 0.4 wt% (Si compound), respectively.

[0155] [Comparative Example 1] Comparative Example 1 was prepared using the same process as in Example 1, except that 2.4 g of titanium dioxide (average primary particle size: 21 nm) from Nippon Aerosil was mixed with 0.6 g of Builddeck (manufactured by Dainippon Paint Co., Ltd.), an acrylic resin and paint, and then ethanol was added to bring the total volume to 300 g.

[0156] [2] Evaluation of porous coatings The following evaluations were performed on the coating solutions (porous coating films, porous coating materials) obtained in the examples and comparative examples.

[0157] (1) Dispersibility (stability) of the dispersion The coating solution (dispersion) was allowed to stand at 60°C for 480 hours. After standing, the dispersion was visually inspected and its dispersion stability was evaluated.

[0158] The criteria for evaluating the coating solution are as follows: ◎: No precipitation, gelation, or other phenomena are observed in the dispersion. ○: Separation is observed in the dispersion, but it disperses easily by stirring by hand. △: Separation is observed in the dispersion, but it can be redispersed by applying external force such as ultrasound. ×: Precipitation and gelation have occurred in the dispersion, and it will not redisperse.

[0159] (2) Contact angle measurement A glass substrate was used as the coating base material, and the coating solution (dispersion) was coated onto the glass substrate using a spin coater at a rotation speed of 1,000 rpm (forming a coating film). The contact angle (°) of the coating film was measured using a contact angle meter (DM400) from Kyowa Interface Science Co., Ltd. in accordance with JIS R 3257.

[0160] (3) Antiviral test After drying, the coating solution (dispersion) was subjected to antiviral testing in the dark using Qβ phage (non-enveloped virus) in accordance with ISO 21702.

[0161] The criteria for determining the antiviral properties of the coating solution are as follows: ◎: The dispersion has an antiviral activity value of 2 or higher. ×: The dispersion has an antiviral activity value of less than 2.

[0162] (4) Check for the presence or absence of rainbow blemishes Using a spin coater, a coating solution (dispersion) was applied to a glass substrate at a rotation speed of 1,000 rpm to create a coating film, and the presence or absence of iridescent unevenness in the coating film was visually checked.

[0163] (5) Measurement of the number of voids in the coating film and the average size of the voids A coating solution (dispersion) is applied to a Si substrate to create a coating film. Images of the coating film are taken using an electron microscope (scanning electron microscope (SEM) or transmission electron microscope (TEM)), and the shape of the coating film is observed at a magnification of 30,000, per unit area of ​​12 μm. 2 Correct (Observation area: 4 μm wide × 3 μm high = 12 μm) 2 The number of voids and the average size of the voids were measured.

[0164] The results of the examples and comparative examples are shown in the table below.

[0165] [Table 1]

[0166] In Examples 1-7, a hybrid composition of silica and titania was obtained using the sol-gel method, and the dispersion stability of the coating solution was good. In Examples 1-7, the coating film was a porous coating film, and a coating material (porous coating film material) was obtained that exhibited excellent antiviral properties, suppressed light interference, and prevented rainbow unevenness.

[0167] In Comparative Example 1, the dispersion stability of the coating solution was poor, and the coating film was not porous.

[0168] [Industrial applicability] This invention relates to a porous coating material produced by the sol-gel method using a hybrid composition of silica and titania, which suppresses light interference and prevents rainbow-like unevenness.

Claims

1. A coating film, (A) Ti compounds and (B) Contains hydrolysis products of alkoxysilanes, The (A)Ti compound has an average primary particle diameter of 1 nm to 50 nm. A porous coating film.

2. The aforementioned coating film is (1) The number of voids was found at a magnification of 30,000x SEM, with a unit area of ​​12 μm². 2 There are over 100 winning tickets. (2) The average size of the voids is 10 nm or more. The coating film according to claim 1.

3. In the coating paint used to form the aforementioned coating film, The (A)Ti compound has a content of 0.01% to 5% by mass, The hydrolysis product of the aforementioned (B) alkoxysilane has a content of 0.01% to 20% by mass. The coating film according to claim 1 or 2.

4. The coating film according to claim 1 or 2, wherein the hydrolysis product of (B) alkoxysilane is the hydrolysis product of tetraethyl orthosilicate (TEOS).

5. The coating film according to claim 1 or 2, which is an antibacterial and antiviral coating film.

6. A method for manufacturing a coating film according to claim 1 or 2, (1) A step of synthesizing a Ti compound in a solvent, attaching an organic chain to the Ti compound, and then producing titania-coated silver, and (2) After step (1), a step of mixing the titania-coated silver to which the organic chain is bonded with an alkoxysilane in a solvent, and then hydrolyzing the alkoxysilane to produce a paint that forms a coating film, and (3) A step of forming a porous coating film using the paint obtained in step (2). A method for manufacturing a coating film, including the method described above.

Citation Information

Patent Citations

  • Antifogging and antifouling glass article

    JP1998231146A

  • Functional inorganic paint and coated product using the same and their use

    JP1998287846A

  • COMPOSITION COMPRISING Ti COMPOUND, Si COMPOUND, AND SOLVENT

    JP2024139342A